Economic Report on Africa 2012 - United Nations (United Nations, 2012)
This publication assesses long-term trends in Africa’s growth, analyses the factors behind the recent growth momentum, and provides global perspectives on the key challenges to be addressed, which are critical to unleashing the role of Africa as a global growth pole. The main aim of this publication is to facilitate discussion on concrete policy directions and actions at both national and regional levels that would help Africa realize its growth potential. As in previous editions, the first part of the report examines recent economic and social developments as well as some selected current and emerging development issues in Africa. The second part focuses on the question of how to address key constraints and unleash the potential of the continent as a new pole of global growth.